Study on Hygiene Practice of the Adult Domestic Household Women Worker in Urban Slum Area of Dhaka City - Uddin, AKM Majbah; Haque, Md Monoarul; Arafat, Yasin; Roy, Suman Kumar; Khan, Md Zahid Hasan; Islam, Khaleda (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Globally, slums have been recognized as neglected communities with limited access to services. They are often characterized by deteriorated or poorly structured houses crowded together, poor environmental managements such as deficient access to safe drinking water and sanitation, stagnation of water, and poor drainage with excessive open sewers, excessive amount of uncollected rubbish, severe overcrowding, flies, and poor lighting. Objective: The purpose of this study was to explore hygiene practice of the adult domestic household women worker in urban slum area of Dhaka city. Methods: This cross sectional study was conducted among adult female domestic household workers ages between 19 to 45 years of the south Monipur slum of Dhaka city. The study was conducted from April 2012 to June 2012. About 95 samples were selected purposively to conduct this study. Results: The mean age of the respondent was 29.32 years. It also found that majority of the respondent (87.37%) were married, 10.53% were separated and 2.11% were divorced. The mean income of the respondent was 2132.63TK. Result found that 76.84% of the respondent use sandal in toilet and 23.16% of the respondent do not use sandal in toilet. It also showed that 69.47% of the respondent use soap everyday in bath and 30.53% of the respondent did not use soap everyday in bath. About 90.53% of the respondent brushing teeth everyday and 9.47% of the respondent did not brush teeth everyday. In addition to this 33.68% of the respondent cut nail regularly and 66.32% of the respondent did not cut nail regularly. Besides 85.26% of the respondent used soap to wash their hand after toilet, 2.11% used ash and 12.63% of the respondent used soil to wash their hand after toilet. Conclusion: The hygiene practice of adult domestic household workers is quite good but the overall practice condition is not in satisfactory state. Further in depth studies are needed to evaluate the actual scenario of the hygiene practice among adult domestic household workers. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22884 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 52-54